Sharia Audit Challenges in Malaysian Islamic Financial Institutions - Shahid, Mohammad; Khaliq, Ahmad; Hassan, Rusni (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2023)
Abstract. Sharia Auditing in Islamic Financial Institutions (IFIs) poses several challenges, for example, lack of standardization, harmonization in Sharia standards, and incompetent Sharia auditors. Addressing these challenges is critical to ensuring the sustainability and growth of IFIs in Malaysia. This study aims to discuss the problems and challenges of Sharia auditing in IFIs. This study used a qualitative method by distributing questionnaires to 40 practitioners from several IFIs engaged in Islamic audit services through a purposive sampling procedure. T he research findings show that the awareness of the Sharia audit is satisfactory in the absence of a separate audit report. In addition, Sharia audit should be integrated into college accounting; comprehensive Sharia audit framework and standards; regulatory/professional bodies; and professional certification in Sharia audit.Abstrak. Audit Syariah di Lembaga Keuangan Islam (LKI) menimbulkan beberapa tantangan, misalnya kurangnya standarisasi, harmonisasi dalam standar Syariah dan auditor Syariah yang tidak kompeten. Mengatasi tantangan ini sangat penting untuk memastikan keberlanjutan dan pertumbuhan LKI di Malaysia. Penelitian ini bertujuan untuk membahas masalah dan tantangan audit syariah di IFI. Penelitian ini menggunakan metode kualitatif dengan menyebar kuesioner kepada 40 praktisi dari beberapa LKI yang bergerak di bidang jasa audit Syariah melalui prosedur purposive sampling. Temuan penelitian menunjukkan bahwa kesadaran audit Syariah cukup memuaskan dengan tidak adanya laporan audit yang terpisah. Selain itu, audit Syariah harus diintegrasikan ke dalam akuntansi perguruan tinggi; kerangka dan standar audit syariah yang komprehensif; badan pengatur/profesional; dan sertifikasi profesi dalam audit Syariah.